Approaches to Evaluating the Quality of IT Project Documentation: A Systematic Literature Review - Unuchak, Yauhen; Unuchak, Tatyana (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This research presents the results of a literature review of methods and approaches to assessing the quality of documentation in IT projects. We conducted a systematic review of about 100 publications devoted to the description of tasks and key elements of project documentation. In this paper we tried to systematize and summarize a) the main approaches and methods used to assess the quality of documentation descriptions in IT projects, b) key criteria and metrics that determine the completeness and clarity of documentation descriptions, c) problems encountered in assessing the quality of documentation and textual descriptions of tasks in IT projects. The obtained results provide a basis for our further work aimed at improving the quality and efficiency of project documentation.